The Impact of COVID-19 Pandemic on Nursing Education among Nursing Students: A Systematic Review - Thandar Soe Sumaiyah Jamaludin; Mohd Said Nurumal; Muhammad Kamil Che Hasan; Nadiah Nurulnasuha Abdul Shukor; Kyu Kyu Win (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2022)
ABSTRACTIntroduction: Globally, the COVID-19 pandemic has had a significant impact on educational sections and is required to close down due to the transmission of the coronavirus.  The newly developed online learning is the most reliable option to resume the education process by preventing the academic calendar from accumulating and minimizing learning loss. Objective: This systematic review aimed to search the available literature on the impact of the COVID-19 pandemic on nursing education. Methods: Searching the literature was systematically done using the PRISMA flow diagram, and the inclusion and exclusion criteria of the study were followed by the PICO/S framework. The quality assessment was conducted by using the CASP. Results Discussion: Three themes emerged in this review. Those are knowledge and perception of the nursing students towards COVID-19, experience and readiness of the nursing students towards E-learning, and the attitude and psychological impact on the nursing students towards COVID-19. ABSTRAKPendahuluan: Secara global, pandemi COVID-19 telah berdampak signifikan pada pendidikan dan diminta ditutup karena penularan virus corona. Pembelajaran online yang baru dikembangkan adalah pilihan yang paling dapat diandalkan untuk melanjutkan proses pendidikan dengan mencegah masa akademik terakumulasi dan meminimalkan kehilangan pembelajaran. Tujuan: Tinjauan sistematis ini bertujuan untuk mencari literatur yang tersedia tentang dampak pandemi COVID-19 pada pendidikan keperawatan. Metode: Penelusuran literatur dilakukan secara sistematis menggunakan diagram alir PRISMA, dan kriteria inklusi dan eksklusi penelitian diikuti dengan kerangka PICO/S. Penilaian kualitas dilakukan dengan menggunakan CASP. Hasil Diskusi: 30 artikel didapatkan setelah proses pencarian. Tiga tema muncul dalam ulasan ini yaitu pengetahuan dan persepsi mahasiswa keperawatan terhadap COVID-19, pengalaman dan kesiapan mahasiswa keperawatan terhadap E-learning, serta sikap dan dampak psikologis mahasiswa keperawatan terhadap COVID-19.